PENERAPAN PIJAT ‘OYOG’ SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN TANDA BAHAYA KEHAMILAN PADA PONED KOTA CIREBON - Suratmi, Suratmi; Mariani, Nina Nirmaya; Sriyatin, Sriyatin (Universitas Padjadjaran, 2025)
Fifteen percent (15%) of pregnant women experience complications during pregnancy; in fact, the number can be even higher. The prevalence of pregnancy complications in Cirebon City reached 26.6%, as out of 5,284 pregnant women, 1,406 experienced complications. The purpose of this activity is to apply the Oyog massage to increase knowledge of pregnancy warning signs. Pregnancy danger signs are problems that must be addressed because they indicate complications that can result in the death of the mother and her baby. The method used is Oyog training for midwives, who will then perform this procedure on pregnant women. The object (target audience) consisted of 5 midwives and 15 pregnant women, with gestational age criteria of 28–30 weeks, no existing pregnancy complications such as hypertension or antepartum hemorrhage, and willingness to participate (mass delivery audience). The facilities used included the Oyog module, which is the result of research output and has obtained an Intellectual Property Rights certificate with No. EC00202035739. There is a difference in knowledge of pregnancy hazards before and after the Oyog procedure, and all midwives are competent in its implementation. The Oyog procedure can be used as a medium to increase knowledge of pregnancy danger signs so that the recognition of complications can be done as early as possible.Lima belas persen (15%) ibu hamil mengalami komplikasi dalam kehamilan, bahkan angkanya bisa lebih dari itu. Komplikasi kehamilan di Kota Cirebon mencapai angka 26,6%, karena dari 5.284 ibu hamil terdapat 1.406 ibu hamil mengalami komplikasi. Tujuan kegiatan ini adalah menerapkan pijat Oyog untuk meningkatkan pengetahuan tanda bahaya kehamilan. Tanda bahaya kehamilan merupakan masalah yang harus diatasi karena tanda bahaya adalah tanda suatu komplikasi dapat mengakibatkan kematian ibu dan bayinya. Metode yang digunakan adalah pelatihan Oyog kepada bidan dan selanjutnya bidan akan melakukan prosedur ini kepada ibu hamil. Objek kegiatan adalah 5 bidan dan 15 ibu hamil, dengan kriteria usia kehamilan 28-30 minggu, tidak memiliki komplikasi dalam kehamilan yaitu hipertensi, perdarahan antepartum serta bersedia menjadi objek (khalayak pengabmas). Sarana yang digunakan adalah modul Oyog hasil output penelitian dan telah mendapatkan sertifikat Hak Atas Kekayaan Intelektual dengan nomor EC00202035739. Terdapat perbedaan pengetahuan tanda bahaya kehamilan sebelum dan setelah Oyog dan seluruh bidan kompeten dalam pelaksanaan Oyog. Prosedur Oyog dapat digunakan sebagai media untuk meningkatan pengetahuan tanda bahaya kehamilan sehingga pengenalan komplikasi dapat dilakukan sedini mungkin.